Strategy to Improve the Performance of Chicken Products through the Development of a Business Model Canvas - Reza, Royhan Aditama Fakhrul; Fontana, Avanti (Jurnal Bisnis dan Kewirausahaan, 2023)
ALIO (name abbreviated for confidentiality) is one of a medium-scale enterprise in Indonesia that engaged in the chicken trading business in Jakarta with the store name is ALIO. This business sells broiler, red, and parent stock chickens. Even though it has been established since 1976, it turns out that the business is still managed in a traditional way so that there were no breakthroughs. Our study aims at analyzing the business model canvas of chicken ALIO. We conducted the study between December 2022 and March 2023. We conducted a business model evaluation based on the SWOT questionnaire (Osterwalder and Pigneur 2020). The findings show that the strength-opportunity level is around 71% and the weakness-threat level is around 63%. This indicated gaps in both sides. The 71% SO needed enhancement. The 63% WO needs reductions. The business coaching approach has resulted in better formation of the business model canvas. The improvement in SO level has become 84% and the improvement of WO level has become 24%. This improvement is a manifestation of adaptive business model to respond to the changing business environment and to enhance business performance. This case study with a business coaching approach has facilitated the process of solving business problems in a focused and involving related entrepreneurs.